Establishing an in-house randomized Taq polymerase library - Li, Siyu (Nanyang Technological University, 2023)
The establishment of an in-house randomized Taq polymerase library is a critical step in the pursuit of improved DNA amplification techniques. Taq polymerase, derived from the thermophilic bacterium Thermus aquaticus, has revolutionized polymerase chain reaction (PCR) due to its thermostability and robustness. This thesis focuses on the establishment of an in-house randomized Taq polymerase library as a valuable resource for directed evolution experiments. Random mutations were introduced throughout the Taq polymerase gene using methods such as error-prone PCR. The His-tag at the N-terminal was even shifted to the C-terminal for optimization of activity. The Taq polymerase was then used in PCRs to amplify specific sequences, of which the products were digested and ligated to be verified for the incorporation of errors. The results of this research provide valuable insights into the generation and application of randomized Taq polymerase libraries for directed evolution and protein engineering. The library represents a valuable resource for future investigations seeking to tailor Taq polymerase properties for specific experimental or application requirements. Additionally, this study enhances our understanding of the structure-function relationships of Taq polymerase and expands the potential applications of this versatile enzyme.